2017
DOI: 10.18370/2309-4117.2017.36.9-12
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining the quality of life and social activity of women in the post-reproductive period

Abstract: Taking into account the increase in the proportion of women in the post-reproductive age in society and the increase in the retirement age, it becomes necessary to preserve their professional and social activity. As of 2016, in the structure of the female population of Ukraine, women over 50 years are 46.7%, respectively, the number of women over 45 years is more than half. However, today the problems of women of post-reproductive age are paid insufficient attention both by society, and by the media and social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…The results obtained prove the need to use prognostic programs to prevent the development of early menopause against the background of biological aging of a woman in order to develop individual preventive measures to preserve her health and improve her quality of life [4,6,11,16]. The use of prognostic models allows timely identification of women at risk of developing this pathology [4,5].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The results obtained prove the need to use prognostic programs to prevent the development of early menopause against the background of biological aging of a woman in order to develop individual preventive measures to preserve her health and improve her quality of life [4,6,11,16]. The use of prognostic models allows timely identification of women at risk of developing this pathology [4,5].…”
Section: Discussionmentioning
confidence: 98%
“…Bromberger, H.M. Kravitz [5] and M. Birhaeuse, A.R. Genazzani [4] have shown that the study and consideration of risk factors for the occurrence of EC allows the development of preventive measures and prescribe individual treatment regimens in advance [6,11,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…На думку А.Б. Камінського, основна відмінність ризику від невизначеності полягає в наявності не ймовірності, а зацікавленої особи, яка перебуває в ситуації неминучого вибору в умовах невизначеності [193].…”
Section: рис 414 інформаційні блоки управлінського обліку на підприєм...unclassified
“…Разом із тим, О. Кіпрєєва ризик порівнює з можливістю отримання додаткового прибутку за позитивних для підприємця умов. Запропоновані визначення поєднують ризик зі збитком, але ці поняття не можна ототожнювати [193]. В.Л.…”
Section: рис 414 інформаційні блоки управлінського обліку на підприєм...unclassified